Development of Android Application-Based Interactive Learning Media on Vehicle Instrument Panel Competence - Nurdiansyah, Ferizal; Sudira, Putu (Universitas Ahmad Dahlan, 2025)
This study aims to: (1) create an interactive learning media product based on Android applications on automotive motor vehicle instrument panel competency; (2) determine the feasibility of learning media based on Android applications on vehicle instrument panel competency. This study is a type of research and development (RnD). The development of this learning media is adapted from the ADDIE (Analysis, Design, Development, Implementation and Evaluation) development model. ADDIE is used to direct the design process as determined. This study was conducted at SMK PIRI 1 Yogyakarta with the research subjects being class XI students of the Automotive Engineering Skills Program. The feasibility test stage for the results of the interactive learning media product was carried out by two material experts and two media experts, as well as trials on end users, namely students. The results of this study are: (1) the creation of an Android application-based learning media product on motor vehicle instrument panel competency; (2) The product feasibility results obtained the category